Efektivitas Video Edukasi Dalam Meningkatkan Pengetahuan dan Sikap Personal Hygiene Remaja Putri - Nur Achfa Aulia Fajariyah; Besse Lidia (Universitas Hang Tuah Pekanbaru, 2026)
Adolescence is a transitional phase that makes young women vulnerable to health problems, especially personal hygiene during menstruation. Lack of knowledge and attitudes about personal hygiene can increase the risk of infection. The aims of this research is to ascertain how well instructional videos can enhance young women's attitudes and understanding around personal hygiene. Thirty female students from SMP Negeri 11 Samarinda were chosen by purposive sampling and split into groups for educational videos and PowerPoint presentations and also the study used a quasi-experimental design with a two-group pretest–posttest. Data were collected through questionnaires before and after the intervention and analyzed using the Wilcoxon Signed Rank and Mann-Whitney U tests. The findings showed a significant increase in knowledge and attitudes in the educational video group (p < 0.001). Educational videos are more effective and are recommended as a learning medium for adolescent reproductive health.